Changing sources of growth in Indian agriculture: Implications for regional priorities for accelerating agricultural growth - Birthal, Pratap Singh; Joshi, Pramod Kumar; Negi, Digvijay S.; Agarwal, Shaily (International Food Policy Research Institute, 2014)
Indian agriculture was transforming from a cereal-based production system toward high-value crops (HVC) during the 1990s. However, food security concerns resurfaced during the first decade of the 21st century, and the policy environment tilted in favor of cereal-based production systems, especially rice and wheat. This paper revisits an earlier study to evaluate how the policy shift influences the patterns and the sources of agricultural growth in India and assesses their implications for regional priorities for higher, more sustainable, and more inclusive agricultural growth.